Frequency of Metabolic Syndrome in Patients with Hypertension (Medical Forum Monthly, 2024)
Objective: To determine the frequency of metabolic syndrome among the hypertensive patients reporting in the outpatient department of a tertiary care hospital.Study Design: Cross-sectional study.Place and Duration of Study: This study was conducted at the Medical OPD of General hospital, Lahore. The present study was conducted from June 2017 to December 2017 over a period of six months.Materials and Methods: Adult known hypertensive patients of age between the ages 19-50 years were included in the study. The patients satisfying the selection criteria of study were incorporated in the study after informed written consent. Physical examination and laboratory investigations were carried out where required. The data was analyzed using SPSS version 16. Mean ± standard deviations (SD) were recorded for quantitative variables while frequencies were obtained for qualitative variables. The level of significance marked by p-value was determined using independent sample t-test and Chi square test respectively. The p-value of ≤0.05 was considered significant.Results: A total of 156 known cases of hypertension were enrolled in the study which included 57(36.54%) males and 99(63.46%) females. The patients were screened for MS using the Adult Treatment Panel III-A (ATP-III-A) criteria. Their blood pressure and waist circumference were recorded and fasting blood samples were drawn to measure serum glucose, HDL-cholesterol and triglyceride levels. MS was found in 65.38% (n=102) patients while 34.36% (n=54) patients did not fulfill the ATP-III-A criteria for MS.Conclusion: MS is highly prevalent among the hypertensive patients and almost two thirds of the study population was found to have MS along with hypertension.